2021
DOI: 10.1002/brb3.2368
|View full text |Cite
|
Sign up to set email alerts
|

Examining the influence of brain stimulation to the medial prefrontal cortex on the self‐reference effect in memory

Abstract: Past work shows that processing information in relation to the self improves memory which is known as the self-reference effect in memory. Other work suggests that transcranial direct current stimulation (tDCS) can also improve memory. Given recent research on self-reference context memory effects (improved memory for contextual episodic details associated with self-referential processing), we were interested in examining the extent stimulation might increase the magnitude of the selfreference context memory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 108 publications
0
4
0
Order By: Relevance
“…Thus, it may be that our finding of a prosocial advantage in memory where participant remember specific details (impressions; behaviors) associated with targets, may be adaptive and help guide future goal-directed behaviors in social contexts. Examining conditions under which memory might be improved is an important pursuit (Bjork & Benjamin, 2011;Burden et al, 2021;Frankenstein et al, 2022;Ilenikhena et al, 2021;Leach et al, 2019;, 2014Leshikar et al, , 2017Matzen et al, 2015), and the results of the current investigation contribute to that empirical goal.…”
Section: In Addition To Finding Improved Impression Memory For Targetsmentioning
confidence: 87%
“…Thus, it may be that our finding of a prosocial advantage in memory where participant remember specific details (impressions; behaviors) associated with targets, may be adaptive and help guide future goal-directed behaviors in social contexts. Examining conditions under which memory might be improved is an important pursuit (Bjork & Benjamin, 2011;Burden et al, 2021;Frankenstein et al, 2022;Ilenikhena et al, 2021;Leach et al, 2019;, 2014Leshikar et al, , 2017Matzen et al, 2015), and the results of the current investigation contribute to that empirical goal.…”
Section: In Addition To Finding Improved Impression Memory For Targetsmentioning
confidence: 87%
“…In addition to improved item memory for lower versus higher constraint conditions, we also found that item memory was better for items processed in both testing conditions (lower, higher constraint) compared to controls (restudy, study‐only), which is consistent with a vast literature showing that testing (or retrieval practice) improves item memory (Adesope et al., 2017 ; Glover, 1989 ; Roediger & Karpicke, 2006 ; Rowland, 2014 ). Finding ways to improve memory is an important scientific endeavor (Bjork & Bjork, 2011 ; Burden et al., 2021 ; Frankenstein et al., 2020 , 2022 ; Ilenikhena et al., 2021 ; Kadwe et al., 2022 ; Leshikar, In Press ; Leshikar et al., 2019 , 2017 ; Leshikar, Park, et al., 2015 ; Matzen et al., 2015 ; Patel et al., 2022 ; Sklenar et al., 2022 , 2021 , 2023 ; Udeogu et al., 2022 ; Urban Levy et al., 2023 ; Villasenor et al., 2021 ), and the results of this investigation add to that cause.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because in the current investigation, participants were making predictions about targets that did not involve the self, which may have made the prediction task lower in self salience. Thus, future work might deploy procedures that enhance the self‐salience of the prediction task, such as those used in investigating memory for self‐relevant information (i.e., self‐reference effects; Brown et al., 1986 ; Burden et al., 2021 ; Gutchess et al., 2007 ; Ilenikhena et al., 2021 ; Jackson et al., 2018 ; Leshikar & Duarte, 2012 , 2014 ; Leshikar & Gutchess, 2015 ; Leshikar et al., 2015 ; Leshikar et al., 2016 , 2017 ; Rogers et al., 1977 ; Symons & Johnson, 1997 ; Wong et al., 2017 ).…”
Section: Discussionmentioning
confidence: 99%